Does mining alleviate or exacerbate poverty: Are local community grievances really 'Much Ado about Nothing'? - Nxele, Musawenkosi (School of Economics, 2017)
This study sets out to evaluate the impact of industrial mining on local economies, within a context of a developing country with a strict procurement policy on its extractive industry. It contributes empirical evidence on two main ideas on the impact of mining on local communities. The one idea is that mining has a positive impact on local communities because it creates economic activity through economic linkages with local markets; and thus contributes to local industrialisation, economic development, and poverty reduction. The other idea is that mining harms local economies through negative impacts on the environment; which hurts local agriculture and health, leading to an increase in local poverty. By evaluating a case study of a poor rural economy driven by mining and agriculture, this study measures the net average impact of the opening and expansion of mining on local income poverty. Using ward level data combined with firm data, the study essentially uses a difference-in-differences estimation procedure, by exploiting a local input demand shock from large industrial mines, as well as changes in distance to a mine, as sources of variation. The study finds that the opening of a mine is associated with poverty reduction in surrounding communities, while the impact from an expansion of a mine depends on the type of commodity mined. Unpacking these results by commodity gives insight into the concentration of labour and community unrest in the platinum and gold mining sectors in South Africa. The findings of this study remain robust to different indicators of mine expansion, and checks for alternative explanations such as selective migration and sample checks. The study uses the Limpopo Province of South Africa as a suitable case study.